Expression of transgenic biotin ligases in inducible neuronal murine cell lines by integration into the mHipp11 gene locus. - Lisa Feicht; Aaron Dangel; Ralf-Peter Jansen (PLoS ONE)
Biotin proximity labeling is a powerful method for identifying proteins associated with a specific organelle, a bait protein, or RNA. It requires the expression of a modified biotin ligase by transient transfection or from a stably integrated expression construct. Because such stable integration of transgenes into stem cells can lead to silencing during differentiation, targeting a biotin ligase to a genomic safe harbor site would be beneficial. Here, we report on the successful targeting and expression of two biotin ligase constructs to the mouse Hipp11 locus during neuronal differentiation. While randomly integrated MicroID and TurboID are expressed and active in mouse embryonic stem cells (mESCs), expression ceases upon differentiation into mESC-derived neurons, which is independent of the promoter used. In contrast, targeting of the same expression cassette to the mHipp11 locus results in expression, correct localization, and biotinylation activity not only in mESCs but also in neurons 8-10 days after differentiation. This demonstrates that the mouse Hipp11 locus is a promising genomic integration site for transgenic biotin ligases in mESCs and mESC-derived neurons.